Factors Influcencing the students satisfaction with e -learning in foreign languages center of Nguyen Tat Thanh University : Thesis for Master degree in business administration ; Code No: 8340101 / Du Mai Quynh ; Tran Ai Cam instructor - Du, Mai Quynh
p 60 - 65